DEM-continuum mechanics coupling simulation of cutting reinforced concrete pile by shield machine. (December 2022) - Liu, Bo; Li, Ting; Han, Yanhui; Li, Dongyang; He, Lulu; Fu, Chunqing; Zhang, Gong
Abstract: Based on the discrete element method (DEM) - continuum mechanics coupling method, a numerical simulation analysis is carried out to model cutting some existing bridge piles that have invaded Beijing Metro Line 12. Firstly, the macroscopic parameters of the reinforced concrete pile and the soil stratum where the shield tunneling machine traversed are calibrated using uniaxial compression and Brazilian test through a series of numerical tests. In this paper, the procedure of building up a DEM-continuum mechanics coupling model is presented, then the model is applied to simulate the process of cutting the pile foundation using the earth pressure balanced (EPB) shield machine. The influences of different advancing parameters on the displacement of the pile bottom, the thrust force, and the torque of the EPB shield machine are investigated. The simulation-calculated results, such as thrust force and torque of the shield machine, are in good agreement with the theoretical method in previous studies and the corresponding monitored data in the field. Finally, a method based on the thrust of a single cutter is proposed to improve the theoretical model so that it can consider the effects of cutting bridge piles.